Studi Komparatif Tentang Talak Di Luar Pengadilan Antara Fatwa Majelis Ulama Indonesia Dengan Kompilasi Hukum Islam - Damayanti, Yunita (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstract: How is the comparative analysis of divorce outside the Court between the Fatwa of the Indonesian Ulema Council and the Compilation of Islamic Law? 2) What is the solution to differences in divorce law outside the court between the fatwas of the Indonesian Ulema Council and the Islamic Law Compilation? The purpose of this study is to find out a comparative analysis of divorce outside the court between the Fatwa of the Indonesian Ulema Council and the Compilation of Islamic Law and find out the solutions to the two differences of opinion regarding the validity of divorce outside the court. These two problems are discussed by using a type of normative legal research with literature studies. The approaches used in this study are a comparative approach, a case approach, a statutory approach, and an analytical approach. The results of this study are: 1) According to the Fatwa Ijtima 'Ulama of the Indonesian Ulema Council IV of 2012 it is explained that divorces carried out by husbands outside the court are legal. Meanwhile, according to the KHI and the marriage law in Indonesia, divorce must be carried out through a trial in a religious court, meaning that divorces made by husbands outside the court are not legally recognized as marriage in Indonesia. 2) The solution to the two differences of opinion is that people prefer to carry out divorces in religious courts which have been regulated by the KHI and marriage law in Indonesia.Keywords: Divorce, MUI fatwas, KHI, and Law No. 1 of 1974 concerning marriage.Abstrak: Analisis komparatif tentang talak di luar Pengadilan antara Fatwa Majelis Ulama Indonesia dengan Kompilasi Hukum Islam? 2) Bagaimana solusi terhadap perbedaan hukum talak di luar pengadilan antara fatwa Majelis Ulama Indonesia dan Kompilasi Hukum Islam? Adapun tujuan dari penelitian ini adalah untuk mengetahui analisis komparatif tentang talak di luar Pengadilan antara Fatwa Majelis Ulama Indonesia dengan Kompilasi Hukum Islam dan mengetahui solusi dari kedua perbedaan pendapat mengenai keabsahan talak di luar pengadilan. Dua permasalahan ini dibahas dengan menggunakan jenis penelitian hukum normatif dengan studi kepustakaan. Adapun pendekatan yang digunakan dalam penelitian ini adalah pendekatan komparatif, pendekatan kasus, pendekatan perundang-undangan, dan pendekatan analisis. Hasil dari penelitian ini adalah:1) Menurut Fatwa Ijtima’ Ulama Majelis Ulama Indonesia IV Tahun 2012 dijelaskan bahwa talak yang dilakukan oleh suami di luar pengadilan adalah sah. Sedangkan menurut KHI dan undang-undang perkawinan di Indonesia bahwa talak harus dilakukan melalui sidang di pengadilan agama, artinya, talak yang dilakukan oleh suami di luar pengadilan tidak diakui secara hukum perkawinan di Indonesia. 2) Solusi dari kedua perbedaan pendapat yaitu agar masyarakat lebih memilih melakukan perceraian di pengadilan agama saja yang sudah diatur oleh KHI dan undang-undang perkawinan di Indonesia.Kata kunci: Cerai Talak, Fatwa MUI, KHI, dan Undang-Undang No.1 tahun 1974 tentang perkawinan.